2008
DOI: 10.1080/15374410802148095
|View full text |Cite
|
Sign up to set email alerts
|

The Transition to Middle School is Associated with Changes in the Developmental Trajectory of ADHD Symptomatology in Young Adolescents with ADHD

Abstract: The Attention Deficit Hyperactivity Disorder (ADHD) symptom presentation of young adolescents with ADHD was examined in association with the transition to middle school. The current study used data collected in the Multimodal Treatment Study of ADHD which included children between 7–9 years of age with a diagnosis of ADHD (n=258) and grade and sex matched controls (n=112). The trajectory of ADHD symptoms before, during and after the transition to middle school was modeled using hierarchical linear modeling. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
0
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 31 publications
7
79
0
6
Order By: Relevance
“…In other words, additional years spent in their adoptive family setting can be regarded as helping adoptees to recover. Finally, as suggested in the previous developmental studies [33], a reduction in ADHD symptomatology with age was found in our sample, but only in the classical hierarchical regression analysis and not when the variance at the adoptee and country levels was taken into account.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…In other words, additional years spent in their adoptive family setting can be regarded as helping adoptees to recover. Finally, as suggested in the previous developmental studies [33], a reduction in ADHD symptomatology with age was found in our sample, but only in the classical hierarchical regression analysis and not when the variance at the adoptee and country levels was taken into account.…”
Section: Discussionsupporting
confidence: 52%
“…a higher prevalence in boys than in girls [46,66]. Age-related differences have also been reported in developmental studies that have found a change in trajectories, with for example a clear reduction in ADHD symptomatology for inattention, hyperactivity and impulsivity at the moment of the transition to middle school for young adolescents [33]. In several studies, ADHD has been found to interfere with adolescents' personal, social and academic development [19,38].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Maedgen and Carlson's participants were between 8 and 11 years of age, whereas our participants were between 12 and 16 years of age. 9 Given that changes in context, expectations, and maturation are associated with differences in the manifestation of ADHD symptoms in childhood versus adolescence (Langberg et al 2008;Wolraich et al 2005), it may be that ED also manifests differently among children and adolescents with ADHD. Another reason for the discrepant findings regarding the relationship between ADHD subtypes and ED may be due to different situations eliciting ED in different subtypes.…”
Section: Subtype Differences In the Association Between Adhd And Edmentioning
confidence: 99%
“…Many of these students reported that during elementary school years they were able to function in ways that lived up to high expectations for academic success that were held by their parents, their teachers and themselves. As was found in the study of Langberg, et al, [51], it was in secondary school settings where they had to keep track of various homework assignments for many different teachers, without anyone to help them to prioritize and remember, that ADHD impairments of these individuals became apparent.…”
Section: Discussionmentioning
confidence: 94%